2007
DOI: 10.1038/nphys812
|View full text |Cite
|
Sign up to set email alerts
|

Efficient coupling of photons to a single molecule and the observation of its resonance fluorescence

Abstract: Single dye molecules at cryogenic temperatures display many spectroscopic phenomena known from free atoms and are thus promising candidates for fundamental quantum optical studies. However, the existing techniques for the detection of single molecules have either sacrificed the information on the coherence of the excited state or have been inefficient. Here we show that these problems can be addressed by focusing the excitation light near to the absorption cross section of a molecule. Our detection scheme allo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
322
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 337 publications
(339 citation statements)
references
References 43 publications
(52 reference statements)
7
322
0
3
Order By: Relevance
“…The corresponding single-atom reflectivity is |r 1 |C0.24, representing an optical attenuation for one atom greater than 40% 12,41 . For comparison, atoms trapped near the surface of a fused silica nanofiber exhibit G 1D C(0.04 ± 0.01)G 0 (refs [27][28][29], comparable with observations with atoms and molecules with strongly focused light 45,46 . By comparing with numerical simulations, our measurements suggest that atoms are guided to unit cells of the PCW by optical dipole forces.…”
supporting
confidence: 79%
See 1 more Smart Citation
“…The corresponding single-atom reflectivity is |r 1 |C0.24, representing an optical attenuation for one atom greater than 40% 12,41 . For comparison, atoms trapped near the surface of a fused silica nanofiber exhibit G 1D C(0.04 ± 0.01)G 0 (refs [27][28][29], comparable with observations with atoms and molecules with strongly focused light 45,46 . By comparing with numerical simulations, our measurements suggest that atoms are guided to unit cells of the PCW by optical dipole forces.…”
supporting
confidence: 79%
“…The measured coupling rate G 1D (quoted absent Purcell enhancement and inhibition due to an external cavity) is unprecedented in all current atom-photon interfaces, whether for atoms trapped near a nanofiber [27][28][29] , one atom in free space 45 , or a single molecule on a surface 46 . For example, in ref.…”
Section: Discussionmentioning
confidence: 99%
“…To saturate such an atomic ensemble and thus produce a nonlinear optical response, a correspondingly large number of photons n ≈ N ≈ d 2 /λ 2 ≈ 1/p is needed. A number of experiments have attempted to maximize the atom-photon interaction probability p by concentrating laser light to a small area, achieving sizeable atom-photon interaction probabilities of p ≈ 0.05 with laser beams focused on neutral atoms 23,24 , p ≈ 0.01 with ions 25 , and p ≈ 0.1 with molecules on a surface 26 .…”
Section: Quantum Nonlinear Optics -Photon By Photonmentioning
confidence: 99%
“…Recent developments in single-molecule spectroscopy have however been able to push the limits of coherent detection under various conditions [19][20][21][22][23]. On the theoretical side, it has been found that there is a profound relationship between the optimal concentration of electromagnetic energy and the strength of light-matter interaction [24,25], pointing out how the possibility of focusing light below the diffraction limit may enhance the detected signal.…”
Section: Introductionmentioning
confidence: 99%